PENGARUH PENGGUNAAN METODE PICTURE AND PICTURE DALAM MENINGKATKAN KEMAMPUAN PEMAHAMAN DAN MOTIVASI BELAJAR SISWA PADA MATERI PERSEBARAN SUMBER DAYA ALAMDAN - Septiana, Mohammad Wildan; Kurnia, Dadang; Irawati, Riana (Jurnal Pena Ilmiah, 2017)
This study has a purpose to compare students' understanding and motivation. The research uses quasi experimental research method with Nonequivalent Control Group Design design. The sample used is the students of grade IV Tenjolaya 1 Elementary School. After the research is known from the significant level Î± = 0.05, 1) Picture and Picture method is considered not better than the conventional method in improving students' understanding and motivation with P-value (Sig 1 -tailed) of 0.068, 2) Picture and Picture method better improve student's learning motivation than conventional method with P-value (Sig. 1-tailed) of 0.002, 3) ability of understanding does not have relation with learning motivation with P-value (Sig. 2-tailed) is worth 0.119. Therefore it is concluded that the Picture and Picture method is not better in improving students 'understanding, but better in improving students' learning motivation than conventional method, and understanding ability has no relation with learning motivation.